Business Schools at the Crossroads? A Trip Back from Sparta to Athens - Murcia, Maria Jose (Journal of business ethics, 2018)
Some business schools have come under considerable criticism for what observers see as their complicit involvement in the corporate scandals and financial crises of the last 15 years. Much of the discussion about changes that schools might undertake has been focused on curriculum issues. However, revisiting the curriculum does not get at the root cause of the problem. Instead, it might create a new challenge: the risk of decoupling the discussion of the curriculum from broader issues of institutional purpose. In this article, we argue that the most pressing need facing business schools is not to teach new courses to be responsive to social demands and stay relevant. Instead, it is to revisit their basic mission—the principles and beliefs on which they were founded—and then to re-evaluate their curriculum design choices in this light. We contrast the Spartan and Athenian educational paradigms as a way of shedding light on the nature of a coherent response.